Retrospective Analysis of Seasonal Changes in Semen Analysis Parameters - Ates, Sinan; Yener, Cem; Arikan, Mehmet Gurkan; Arda, Ersan; Cokay, Deniz; Elter, Koray (Gynecology Obstetrics & Reproductive Medicine, 2023)
OBJECTIVE: Seasonal and environmental temperature changes may affect semen analysis results. This study aimed to evaluate the effect of seasonal changes on semen analysis parameters. STUDY DESIGN: Cross-sectional study conducted at Trakya University Faculty of Medicine, Department of Obstetrics and Gynecology, Edirne, Türkiye. Data from 2055 semen analyses collected between January 2014 and December 2019 from 1358 patients living in the Thrace region of Türkiye were analyzed retrospectively. Sperm analysis was performed according to 2010 WHO criteria. RESULTS: Sperm concentration was significantly higher in autumn months compared to spring and summer months (p<0.05). The total motility rate of sperm was significantly lower in winter months compared to other months (p<0.05). No statistically significant seasonal differences were observed in semen volume or morphology (p>0.05). CONCLUSIONS: Our study showed that seasonal changes in semen analysis parameters, including peak sperm concentrations in autumn and low motility rates in winter, may be related to air temperature, daylight duration, etc., and may prompt further study of environmental conditions on male fertility.